Penetapan Kadar Antosianin Dan Formulasi Sediaan Blush On Compact Powder Ekstrak Beras Merah (Oryza Rufipogon Griff.) - Rikawati Fitriana (Jurnal Medika Nusantara, 2023)
Blush or rouge is one of the decorative cosmetic preparations in beauty products that is widely used by presenting various colors as coloring the cheeks with an artistic touch so as to enhance aesthetics in the nuances of make-up on the face, giving a thinner and fresher accent to the face. One of the natural ingredients that can be used as a dye is Red Rice (Oryza rufipogon Griff.) Red Rice (Oryza rufipogon Griff.) is rice that contains anthocyanin compounds which function to give red color to red rice. This study aims to determine whether brown rice can be used as a coloring agent for blush on compact powder form and to determine the physical evaluation of blush preparations. The formulation of the blush preparation was made using dyes from red rice extract with a concentration of 0%, 5%, 10% and 15%. This research method was carried out experimentally, including: sample preparation, simplicia characterization, extract preparation, phytochemical screening, determination of anthocyanin levels, preparation of preparations. extraction was carried out by maceration and remaceration, using 96% ethanol solvent, then concentrated with a rotary vacuum evaporator. Tests carried out on the physical evaluation of blush on preparations included organoleptic tests, homogeneity tests, pH tests, irritation tests, adhesion / spread tests, crack tests, hedonic (preferability) tests and stability tests. The results of organoleptic testing, homogeneity, pH test, irritation test showed that all formulas were good. In the fracture test results of the 4 formulas it was observed that they were not cracked, cracked, and broken. The results of the hedonic (preference) test for blush with brown rice extract show that on average the ease of use of blush is preferred. The stability test results at room temperature (20-25oC) did not change, the stability test results at refrigerator temperature (5oC), oven temperature (40oC), and temperature to electric light (30oC) underwent changes.